Fissarcturus walteri sp. nov. from the Ross Sea of the Southern Ocean (Isopoda, Antarcturidae) - Brandt, Angelika (Zootaxa, 2013)
During the Victoria-Land Transect project two specimens of a new species, Fissarcturus walteri sp. nov., were found in the Ross Sea along the Victoria Land Coast, Antarctica, during the 19th Italica expedition in February 2004. This is the second species of Fissarcturus from the Ross Sea after F. rossi Brandt, 2007. F. walteri sp. nov. is most similar to Fissar-cturus granulosus (Nordenstam, 1933) from South Georgia but can be distinguished by the blunt short, anteriorly directed supraocular spines and elevations and some other characters as described herewith.